2024
DOI: 10.1111/nph.19605
|View full text |Cite
|
Sign up to set email alerts
|

Spores of arbuscular mycorrhizal fungi host surprisingly diverse communities of endobacteria

Olga A. Lastovetsky,
Tancredi Caruso,
Fiona P. Brennan
et al.

Abstract: Summary Arbuscular mycorrhizal fungi (AMF) are ubiquitous plant root symbionts, which can house two endobacteria: Ca. Moeniiplasma glomeromycotorum (CaMg) and Ca. Glomeribacter gigasporarum (CaGg). However, little is known about their distribution and population structure in natural AMF populations and whether AMF can harbour other endobacteria. We isolated AMF from two environments and conducted detailed analyses of endobacterial communities associated with surface‐sterilised AMF spores. Consistent with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…All the AMF spores analysed by microscopy (ca. 30 spores) revealed the presence of endofungal bacteria, suggesting a high prevalence of these symbionts in AMF, as shown in different environments (Lastovetsky et al, 2018 , 2024 ).…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…All the AMF spores analysed by microscopy (ca. 30 spores) revealed the presence of endofungal bacteria, suggesting a high prevalence of these symbionts in AMF, as shown in different environments (Lastovetsky et al, 2018 , 2024 ).…”
Section: Resultssupporting
confidence: 52%
“…Studies focused on the interactions of AMF with microorganisms revealed, since 1970 (Mosse, 1970 ), that some AMF harbour morphologically diverse lineages of endofungal bacteria (Agnolucci et al, 2019 ; Araldi‐Brondolo et al, 2017 ; Bianciotto et al, 1996 , 2000 ; Bonfante & Anca, 2009 ; Lumini et al, 2007 ; Scannerini & Bonfante, 1991 ; Uehling et al, 2023 ). Most of the endofungal bacteria hitherto reported in Glomeromycotina have been classified into two main lineages: BRE for Burkholderia ‐related endobacteria and MRE for Mycoplasma ‐related endobacteria (Bianciotto et al, 2003 ; Naito et al, 2017 ; Naumann et al, 2010 ) being MRE most diverse and frequent in AMF than BRE (Lastovetsky et al, 2018 , 2024 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adding a protist to the experimental system was shown to further increase the nitrogen gained by the AM fungus by at least 65% (Rozmoš et al 2022), which illustrates how trophic complexity within microbial communities can enhance nutrient availability and ultimately, host plant performance. Lastly, a recent study by Lastovetsky et al (2024) found that a single AM fungus spore can contain up to 227 endobacterial taxa, most of which have unknown functions but are proposed to be both parasitic and conditional mutualists.…”
Section: Teams Evolve Because Of Selection For Functions That Enhance...mentioning
confidence: 99%